2019
DOI: 10.1002/adts.201900069
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Bonding Effect on the Incorporation and Conduction of Interstitial Oxide Ions in Gallate Melilites

Abstract: The ability to incorporate high content of interstitial oxygen ions (O i ) in La 1+x Sr 1-x Ga 3 O 7+0.5x melilite owing to the good size match between La 3+ and Sr 2+ ions is well documented. Here, the complete substitution of Sr 2+ by Pb 2+ lone-pair cations results in a significant loss of this ability, even though Sr 2+ and Pb 2+ have almost the same effective ionic radius. To explore the fundamental mechanism underlying this result, density functional theory (DFT) calculations are performed on both the La… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 28 publications
3
14
0
Order By: Relevance
“…[9] Therefore, the interstitial oxygen site in the melilite oxide ion conductors is still controversial. More recently, we and Schuett et al carried out density functional theory (DFT) calculations on La 1.5 Sr 0.5 Ga 3 O 7.25, [25,26] respectively, which showed that the interstitial oxygen position obtained from geometry optimization indeed is consistent with the interstitial oxygen site close to the pentagonal ring center determined by our previous structural analysis of La 1.54 Sr 0.46 Ga 3 O 7.27 based on the NPD data. Schuett et al further studied locally various La/Sr cation environments in the melilite structure, which showed there are slightly offcentered positons depending on the local La/Sr cation environments.…”
Section: Diversity Of Interstitial Oxide Ion Stabilization Mechanismsupporting
confidence: 57%
See 4 more Smart Citations
“…[9] Therefore, the interstitial oxygen site in the melilite oxide ion conductors is still controversial. More recently, we and Schuett et al carried out density functional theory (DFT) calculations on La 1.5 Sr 0.5 Ga 3 O 7.25, [25,26] respectively, which showed that the interstitial oxygen position obtained from geometry optimization indeed is consistent with the interstitial oxygen site close to the pentagonal ring center determined by our previous structural analysis of La 1.54 Sr 0.46 Ga 3 O 7.27 based on the NPD data. Schuett et al further studied locally various La/Sr cation environments in the melilite structure, which showed there are slightly offcentered positons depending on the local La/Sr cation environments.…”
Section: Diversity Of Interstitial Oxide Ion Stabilization Mechanismsupporting
confidence: 57%
“…The geometry optimization for indeed confirmed the relaxation of framework atoms in the defect structure solved from NPD data. [25] These electronic structure calculations provided new insight into the accommodation and migration of oxygen interstitials in La 1 + x Sr 1-x Ga 3 O 7 + 0.5x melilites. Interstitial oxide ions in the site close to the center of the pentagonal ring allows the formation of a covalent bond with one 3-connected tetrahedral Ga2a (Figure 6a-c).…”
Section: Chemical Bonding Effectmentioning
confidence: 95%
See 3 more Smart Citations